Moist extrusion of soy products influences growth performance and nutrient utilization in the early-weaned pig - K G Friesen; Jim L Nelssen; Robert D Goodband; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1992)
One hundred and seventy pigs (initially 12.81b and 21 d of age) were used to determine the effect of moist extrusion on soybean products when fed to the early-weaned pig. Dietary treatments, including a positive control, fed d 0 to 14 postweaning were arranged in a 2 x 3 factorial. Pigs were fed one of the seven diets: 1) control diet (milk): corn+dried skim milk+dried whey+casein; 2 and 3) corn+defatted soy flakes with or without moist extrusion; 4 and 5) corn+toasted soy flour with or without moist extrusion; and 6 and 7) corn+ soy protein concentrate with or without moist extrusion. The diets were formulated to 1.4% dietary lysine and 24.4% lactose, with soy products and purified lactose replacing the milk products on an isolysine and isolactose basis. From d 14 to 35 postweaning, all pigs were fed a common (1.25% lysine) corn-soybean meal diet containing 10% dried whey and 4% select menhaden fish meal. Pigs fed extruded soy products had improved ADG, ADFI, and FIG compared to pigs fed nonextruded soy products, with the largest improvement in pigs fed extruded soy flakes and flour. Dry matter and N digestibilities also were greater in pigs fed extruded soy products compared to pigs fed nonextruded soy products. When pigs were fed a common diet (d 14 to 35), ADFI and FIG were improved in pigs fed a nonextruded soy product from d 0 to 14 than in pigs fed an extruded soy product. Cumulative (d 0 to 35) ADG, ADFI, and F/G were improved in pigs fed extruded soy products compared to pigs fed non- extruded products. These data suggest that growth performance of early-weaned pigs fed less refined soy products (soy flakes and soy flour) processed by moist extrusion can be comparable to that of pigs fed highly refined soy products (soy protein concentrate).; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Pigs; Soy protein; Moist extrusion; Nutrient digestability